Diagnosing primary immunodeficiency: a practical approach for the non-immunologist. (27th February 2015) - Lehman, Heather; Hernandez-Trujillo, Vivian; Ballow, Mark
Abstract: Objective: This review will provide an overview of the most common clinical presentations of primary immunodeficiency (PI), navigating through various affected organ systems. The goal is to accurately portray the high variability of this disease and provide a resource that helps to raise the index of suspicion of PI among physicians, aid in recognition of various PI disorders, and trigger more frequent screenings with appropriate referrals to immunologists for further evaluation and treatment. Summary: Patients with PI comprise more than 200 defined genetic abnormalities. Patients have an array of clinical manifestations, ranging from the most widely associated recurrent and chronic bacterial infections to other associated comorbid conditions involving many organ systems. There is still considerable delay between the onset of symptoms and the time of diagnosis of PI. This review will present an overview of the clinical manifestations that will enhance a physician's recognition of a possible PI. Particular emphasis is placed on the pathogens associated with the specific arm of the immune system that is related to each particular type of PI. The initial immune evaluation is described, which together with the history and physical exam can help focus the physician on the immune compartment most likely associated with a PI. Conclusions: Understanding the types of PI and the related clinical manifestations can help physicians see beyond the presenting symptoms and lead to improved recognition and diagnosis of PI. Timely diagnosis is of utmost importance in PI, as recent advances in bone transplantation and immunoglobulin replacement therapy, as well as future gene therapies, provide effective ways to prevent significant mortality and morbidity.